Category theory for the sciences - Spivak, David I., 1978- (The MIT Press, 2014)
An introduction to category theory as a rigorous, flexible, and coherent modeling language that can be used across the sciences.
Keywords: Science -- Mathematical models.; Categories (Mathematics); elektronické knihy; electronic books